2021
DOI: 10.1126/science.abj8723
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “An early Miocene extinction in pelagic sharks”

Abstract: Sibert and Rubin (Reports, 4 June 2021, p. 1105) report an early Miocene extinction in pelagic sharks based on the loss of shark denticle diversity in two widely separated deep-sea sediment cores. We assert that the pattern observed is not a consequence of extinction but results from shifting species ranges induced by global current reorganization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Sibert and Rubin [16] used dermal denticles as vehicles for studying changing abundances of sharks through geological time. The use of solitary denticles, however, incurs the risk of overestimating the extent of interspecific variation due to the diversity of denticle morphotypes, which vary considerably during ontogeny and around the body, as suggested by other authors [60,61], as well in our study. Denticles can be present around the eye [62] and inside the mouth [20,63], and the homology of denticle and tooth developmental patterning is a recent focus of analyses of gene-expression patterns [64,65].…”
Section: Discussionmentioning
confidence: 42%
“…Sibert and Rubin [16] used dermal denticles as vehicles for studying changing abundances of sharks through geological time. The use of solitary denticles, however, incurs the risk of overestimating the extent of interspecific variation due to the diversity of denticle morphotypes, which vary considerably during ontogeny and around the body, as suggested by other authors [60,61], as well in our study. Denticles can be present around the eye [62] and inside the mouth [20,63], and the homology of denticle and tooth developmental patterning is a recent focus of analyses of gene-expression patterns [64,65].…”
Section: Discussionmentioning
confidence: 42%
“…The placoid scales described here cannot easily be ascribed to any of the taxa based on dermal denticles raised by Johns et al (1997), whose work forms the foundation for taxonomic assignment of placoid scales from the Permian and Triassic of China. Moreover, placoid scales display different morphologies across the body and the number of placoid scale-based genera and species might significantly surpass the actual number of taxa (Naylor et al, 2021). Nevertheless, the placoid scales in this study display the characteristic features found in hybodontiform rather than neoselachian sharks, supporting our general taxonomic assignment here.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and arrangement of placoid scales can be species-specific and is often used in species identification (Reif, 1985b;Raschi and Tabit, 1992;Deynat, 2000;Gravendeel et al, 2002;Claes and Mallefet, 2009;Dillon et al, 2017;Ferroń and Botella, 2017;Ankhelyi et al, 2018;Duchatelet et al, 2020a). Intraspecific variation of placoid scale morphology is observed at different body regions (Duchatelet et al, 2020a;Feichtinger et al, 2021;Gabler-Smith et al, 2021;Naylor et al, 2021) but, within a dedicated body region, the intraspecific variation is low (authors' pers. obs.).…”
Section: Introductionmentioning
confidence: 99%